The Main Functions of the Passive Voice in the Text - Kilanava, Ema (COLLECTION OF SCIENTIFIC WORKS OF SOKHUMI UNIVERSITY, 2023)
The problem of the wide use of the passive constructions in modern English has been touched upon in the works of many authors as the passive voice is principally significant for the entire system of the English language as well as for the whole system of the English verb. The present article gives a critical survey of the linguistic literature on the functions of the passive voice and the causes predetermining the choice of the passive constructions in the text.